Ethical Dimensions of the Foreign Policy of the European Union : A Legal Appraisal - Khaliq, Urfan (Cambridge University Press, 2013)
In their foreign policies states have historically, in the main, sought directly to protect only their own interests. During the last thirty years or so, various administrations have formally declared that in their foreign policy formulation, acting either individually or collectively, they will take account of human rights, good governance and democracy, among other values